2015
DOI: 10.5455/2349-3291.ijcp20150204
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, pathogen profile and outcome of ventilator associated pneumonia in a Neonatal intensive care unit

Abstract: Ventilator-Associated Pneumonia (VAP) is defined as nosocomial pneumonia in mechanically ventilated patients that develop more than 48 hours after initiation of Mechanical Ventilation (MV). 1 In addition to its high mortality rate compared to other nosocomial infections, VAP is associated with prolonged hospitalisation and considerable medical costs. Intubation associated lesions of pharynx and trachea lead to bacterial colonization by decreasing ciliary function and swallowing reflex. It inhibits cough reflex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…The study results found that nearly two-thirds of VAP infants had nasogastric tube either for decompression or for feeding; these results were in accordance with [24] , also with [32] who mentioned that, the presence of nasogastric tube statistically significant risk factor of VAP. The current study results revealed that more than two-fifth of VAP infants received enteral feeding, these study results in accordance with [20] who reported that, more than half of VAP group received enteral feeding.…”
Section: Discussionsupporting
confidence: 89%
“…The study results found that nearly two-thirds of VAP infants had nasogastric tube either for decompression or for feeding; these results were in accordance with [24] , also with [32] who mentioned that, the presence of nasogastric tube statistically significant risk factor of VAP. The current study results revealed that more than two-fifth of VAP infants received enteral feeding, these study results in accordance with [20] who reported that, more than half of VAP group received enteral feeding.…”
Section: Discussionsupporting
confidence: 89%
“…One of the major risk factors for VAP is the duration of MV [37,42,49]. Oral secretions accumulate in the posterior pharynx of the intubated patient as a result of their impaired swallowing.…”
Section: Endotracheal Intubation Suction Practices and Early Extubationmentioning
confidence: 99%